Prevalence of Corneal Astigmatism before Cataract Surgery in Caucasian Patients. Issue 4 (July 2014) - De Bernardo, Maddalena; Zeppa, Lucio; Cennamo, Michela; Iaccarino, Stefania; Zeppa, Lucia; Rosa, Nicola
Purpose: To analyze and quantify the pattern of corneal astigmatism in patients awaiting cataract surgery to provide information for cataract surgeons and intraocular lens (IOL) manufacturers and to establish the demand for toric IOLs in a hospital. Methods: This cross-sectional retrospective study evaluated keratometric (K) values measured by partial coherence interferometry (IOLMaster) in cataract surgery candidates, who were then analyzed and correlated by age and axial length (AL) ranges. Results: The study evaluated the K values in 757 eyes of 380 patients with a mean age of 71.9 ± 10.2 years (range 33–96 years). The mean corneal astigmatism was 1.02 ± 0.69 D (range 0.06–4.57 D). It was 1 D or higher in 316 (41.74%) eyes. The mean AL was 23.56 ± 1.35 mm (range 20.53–31.86 mm). Conclusions: Our study shows that roughly 50% of the eyes have more than 1 D of astigmatism. The results can help hospitals plan and analyze the amount and costs of using toric IOLs in patients with corneal astigmatism.